Global logistics and supply chain management - Mangan, John (Wiley, 2015)
Logistics and Supply Chain Management (SCM) are the areas of study which help us to explore and answer these questions. Today they play a very important role in underpinning the success of many organisations across the public and private sectors and impact how we live our lives. While the origins of logistics and SCM are firmly embedded in the manufacturing domain, the successful applications of logistics and SCM principles and practices are becoming increasingly relevant in the services area also – see for example, the many changes that have recently been driven into healthcare systems and airlines.